Hargrove's Ontological Argument for the Aesthetic Foundation of Wilderness Preservation: Comment from a Chinese Philosophical Perspective - Gao, Shan (Environmental ethics, 2024)
Hargrove's ontological argument for Aesthetic Foundation of Wilderness Preservation was the extension of the thinking paradigm from human beings to moral consideration and aesthetic appreciation of wilderness. The thinking paradigm was based on the framework of traditional Western philosophy, which includes metaphysics, epistemology, and ethics. In this article, I will examine Hargrove's ontological argument by making a little comparison with the perspective of a Chinese philosophical framework. This paper will be divided into three parts. In the part I, I will summarize Hargrove's ontological argument for natural beauty and environmental preservation. In part II, I will examine the metaphysical framework in Hargrove's ontological argument. I argue it is the extension of Plato's metaphysics of the ultimate reality to wilderness. In Part III, I will examine the ethical and aesthetic framework in his ontological argument. I point out Hargrove's ethical framework comes from ethical rationalism and his aesthetic framework is the legacy of Plato's aesthetics. By comparison, Chinese metaphysics stresses the process and Chinese ethics stresses care. The two different directions promote the aesthetic appreciation of agricultural land rather than wilderness.